2009
DOI: 10.1016/j.ultramic.2009.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Removal of histone tails from nucleosome dissects the physical mechanisms of salt-induced aggregation, linker histone H1-induced compaction, and 30-nm fiber formation of the nucleosome array

Abstract: In order to reveal the roles of histone tails in the formation of higher-order chromatin structures, we employed atomic force microscopy (AFM), and an in vitro reconstitution system to examine the properties of reconstituted chromatin composed of tail-less histones and a long DNA (106-kb plasmid) template. The tail-less nucleosomes did not aggregate at high salt concentrations or with an excess amount of core histones, in contrast with the behavior of nucleosomal arrays composed of nucleosomes containing norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…Core histones were purified from HeLa cells according to the method developed by O'Neill et al [14] with slight modifications [34].…”
Section: Dna and Histonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Core histones were purified from HeLa cells according to the method developed by O'Neill et al [14] with slight modifications [34].…”
Section: Dna and Histonesmentioning
confidence: 99%
“…Instead, we used positively charged mica surface that had been treated with spermidine before sample deposition [34,[36][37][38]. The reconstituted nucleosomal array was diluted to a concentration of 0.5 ng/ml in a buffer containing 5 mM HEPESNaOH (pH 7.5) and 50 mM NaCl, and 3 ml of the sample was immediately deposited onto freshly cleaved 1 mm 2 mica discs pretreated with 10 mM spermidine.…”
Section: Fast-afm Observationmentioning
confidence: 99%
“…The importance of the N-terminal histone tail in chromatin structure has been also investigated (Hizume et al, 2009). In vitro chromatin reconstitution using tail-less histones is efficient, but interactions between histones are weaker than using full histones.…”
Section: Histone and Higher Foldingmentioning
confidence: 99%
“…In our previous studies, we analyzed chromatin structures reconstituted from tail-less or hyper-acetylated HeLa core histones [27,28]. In these studies, it was observed that the interaction between nucleosomes decreased both by hyper-acetylation and removal of the tails.…”
Section: The Effect Of Histone-tail On "Salt-induced Aggregation" Andmentioning
confidence: 99%
“…Salt-dependent precipitation of nucleosomal array revealed that acetylation of histone H4 [20] (or H2B and H4 [21]) is sufficient to inhibit chromatin compaction. AFM observation had also revealed that the reconstituted nucleosomal array using tail-less or hyper-acetylated core histones did not show salt-induced compaction [22].…”
Section: Introductionmentioning
confidence: 99%